2021
DOI: 10.1007/s40121-021-00567-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Regression of Herpes Zoster Incidence Worldwide

Abstract: Introduction Many studies have been conducted worldwide to estimate herpes zoster (HZ) incidence rates. We synthesized studies of HZ incidence rates in the general population using meta-analysis models. Methods A random effects meta-analysis was conducted to estimate HZ incidence from a published worldwide systematic literature review (SLR) including only individuals aged 50 years and older. Meta-regression was used to explore whether variability in incidence rates coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“… 12 , 26 In addition, a recent meta-analysis of HZ incidence worldwide reported that IRs for HZ were numerically lower in Europe (IR, 6.77; 95% CI, 6.14-7.48) compared with North America (IR, 7.33; 95% CI, 6.26-8.58). 27 The increased risk of HZ in North America vs Europe may reflect differences in vaccination recommendations or vaccine uptake, and/or HZ incidence across these regions. Alternatively, this finding may reflect some other, as yet unidentified, confounding factor, and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 26 In addition, a recent meta-analysis of HZ incidence worldwide reported that IRs for HZ were numerically lower in Europe (IR, 6.77; 95% CI, 6.14-7.48) compared with North America (IR, 7.33; 95% CI, 6.26-8.58). 27 The increased risk of HZ in North America vs Europe may reflect differences in vaccination recommendations or vaccine uptake, and/or HZ incidence across these regions. Alternatively, this finding may reflect some other, as yet unidentified, confounding factor, and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The aging of the population increases the incidence of HZ worldwide, especially Asia [ 2 ]. Studies have shown that the incidence of HZ is 3–5/1000 person-years in the general global population [ 3 , 4 ] and 2.9–5.8/1000 person-years in 50-year-old individuals in mainland China [ 5 ]; this rate of incidence is increasing by 2.5–5.0% every year [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the global incidence of herpes zoster in the general population is 3–5‰ [ 31 ], which is about 9–34%, and PHN occurs in more than 50% of patients with herpes zoster [ 32 ]. The clinical manifestations of PHN include sleep and emotional disorders in addition to pain.…”
Section: Discussionmentioning
confidence: 99%